2022
DOI: 10.1038/s41419-022-04852-3
|View full text |Cite
|
Sign up to set email alerts
|

PRKDC promotes hepatitis B virus transcription through enhancing the binding of RNA Pol II to cccDNA

Abstract: Hepatitis B virus infection remains a major health problem worldwide due to its high risk of liver failure and hepatocellular carcinoma. Covalently closed circular DNA (cccDNA), which is present as an individual minichromosome, serves as the template for transcription of all viral RNAs and pla ays critical role in viral persistence. Therefore, there is an urgent need to gain broader insight into the transcription regulation of cccDNA. Here, we combined a modified Clustered Regularly Interspaced Short Palindrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Later on, both ATM and ATR were described as enhancing HBV replication (Kostyusheva et al, 2019), and the ATR/Check1 pathway shown to up-regulate cccDNA formation (Luo et al, 2020a). More recently, DNA-PK was described to increase HBV transcription (Fan et al, 2022). In our analyses, these three kinases were predicted to be activated upon HBV infection, as soon as 2- and up to 7-dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, both ATM and ATR were described as enhancing HBV replication (Kostyusheva et al, 2019), and the ATR/Check1 pathway shown to up-regulate cccDNA formation (Luo et al, 2020a). More recently, DNA-PK was described to increase HBV transcription (Fan et al, 2022). In our analyses, these three kinases were predicted to be activated upon HBV infection, as soon as 2- and up to 7-dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, both ATM and ATR were described as enhancing HBV replication ( Kostyusheva et al, 2019 ), and the ATR/Check1 pathway shown to upregulate cccDNA formation ( Luo et al, 2020a ). More recently, DNA-PK was described to increase HBV transcription ( Fan et al, 2022 ). In our analyses, these three kinases were predicted to be activated upon HBV infection, as soon as 2- and up to 7-dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Under the supercoiling stress of transcription (Ma and Wang, 2016), centromeres may produce different types of DNA structures (Kasinathan and Henikoff, 2018) as well as mismatches between repeats. In the centromere associated proteins, both Mre11 and Prkdc can take functions on specific DNA structures (D'Amours and Jackson, 2002;Fan et al, 2022) and Mlh1 is a key player for mismatch repair. The loading of these DNA Frontiers in Genetics frontiersin.org repair proteins to centromeres might be beneficial for the maintenance of centromere stability.…”
Section: Discussionmentioning
confidence: 99%